Controlling conservation functions of peat lands at Langgam Sub District, Pelalawan of Riau Province - P Astuti; C A Bintang (Journal of Degraded and Mining Lands Management, 2015)
Forest fires in Langgam District, Pelalawan Regency of Riau Province is caused environmental damage which impact on many aspects, especially the social and economic. This study was aimed to identify the natural environment, the impact of deforestation and land, and the potential problems to the spatial environment and to manage of land conservation and the environment. The methodology used in this study-included quantitative analysis with interviews, GIS spatial analysis and qualitative analysis. Results of this study indicated that the destruction of forests covering about 45.71% of total land in Riau Province was peat land. Sixty six percent of the destruction was directed to the use of land and forest production. There were 11 fire spots in the Langgam District. Results of SWOT analysis indicated non-integrated the estate management, lack of coordination among stakeholders, non-integrated institutional management and forestry and plantations, lack of budget, large illegal logging and land conversion made by private and public institutions.